Lawrence in Arabia : war, deceit, imperial folly and the making of the modern Middle East - Anderson, Scott, 1959- (New York : Doubleday, 2013)
A narrative chronicle of World War I's Arab Revolt explores the roles of a small group of adventurers and low -level officers who orchestrated a secret effort to control the Middle East, demonstrating how they instigated jihad against British forces, built an elaborate intelligence ring and forged ties to gain valuable oil concessions.
Playboys in the holy land -- A very unusual type -- Another and another nice thing -- To the last million -- A despicable mess -- The keepers of secrets -- Treachery -- The battle joined -- The man who would be kingmaker -- Neatly in the void -- A mist of deceits -- An audacious scheme -- Aqaba -- Hubris -- To the flame -- A gathering fury -- Solitary pursuits -- Damascus -- Epilogue: Paris.
Maps on lining papers.
Includes bibliographical references (pages [543]-552) and index.
Keywords: Lawrence, T. E. -- 1888-1935.; Great Britain. -- Army -- Biography; World War, 1914-1918 -- Campaigns -- Middle East; World War, 1914-1918 -- Campaigns -- Turkey; Soldiers -- Great Britain -- Biography; Middle East -- History -- 1914-1923.